Studies of Bulbophyllum (Orchidaceae) in eastern Indochina Ⅳ. New species in the flora of Laos and Vietnam - Averyanov, Leonid; Dat, Pham Thi Thanh; Truong, Ba Vuong; Orlov, Nicolai; Maisak, Tatiana; Nguyen, Tuan Hoang; Dinh, Quang Diep (Phytotaxa, 2021)
The paper provides a short review of Bulbophyllum species recorded in Laos and Vietnam during the two last decades and continues the publication of results of our successive studies of the genus in this area. It presents data on two new species for science discovered in Laos (Bulbophyllum pachypodum) and Vietnam (B. neglectipetalum), one lesser known species for the flora of Laos (B. microtepalum), two new records for the flora of Vietnam (B. echinulus, B. setilabium), and new illustrated data on B. secundum insufficiently known in the flora of Vietnam. Bulbophyllum fascinator earlier accepted in specific rank reduced into the synonymy of B. putidum on the base of studies of newly obtained materials. Taking into consideration the new data presented in this paper, the flora of Laos presently includes 85, and flora of Vietnam 151 Bulbophyllum species, excluding Monomeria, Trias, and Sunipia. It is the largest genus in the orchid floras of both countries.